A Step toward a Conceptualization of Transnational Disability: Engaging the Dialectics of Geopolitics, “Third World,” and Imperialism - Kazemi, Sona (Critical Disability Discourses, 2017)
This article is a summary of one part of a larger project, which studied war and the resulting production of disabled bodies, analyzed in a dialectical (i.e., not linear, oppositional, binary, idealist, or mechanical) and historical materialist framework. This article comprises a summarized report of one aspect of a case study and a new conceptualization of disability theory from a transnational perspective. The case study examines the social relations behind the production of disabled bodies in the Iran-Iraq war, in which chemical weapons of mass destruction were used. The second part of the article, using the case study report, develops an anti-racist, anti-imperialist, anti-nationalist, and non-ideological (according to Marx’s Consciousness Theory) model for understanding disability.[1]This study uses the global context of capitalist economy and the imperialist politics of the United States and Europe in the Middle East to understand how disabled bodies are generated through armed conflicts sustained by imperialist and nationalist social relations (always gendered, raced, and classed). This study engages the dialectics of geopolitics, examines them in the context of war, and proposes a new emerging model for Disability Studies from a war-survivor Middle Eastern woman’s standpoint. Keywords Non-ideological; Iran-Iraq war; disabling imperialism; disabling nationalism; transnational disability model; Third World Un pas vers une conceptualisation du modèle de handicap transnational: Engager la dialectique de la géopolitique, du « tiers-monde » et de l’impérialisme Résumé Cet article est un résumé d’un projet beaucoup plus vaste, qui étudie la guerre et la production résultante de corps handicapés, analysée de façon dialectique (c’est-à-dire non linéaire, oppositionnel, binaire, idéaliste ou mécanique) et d’un travail matérialiste historique. Cet article comprend un rapport résumé d’une étude de cas et une nouvelle conceptualisation de la théorie du handicap dans une perspective transnationale. L’étude de cas examine les relations sociales derrière la production de corps handicapés durant la guerre Iran-Irak, dans laquelle des armes chimiques de destruction massive ont été utilisées. La deuxième partie de cet article, en utilisant le rapport d’étude de cas, développe un modèle antiraciste, anti-impérialiste, antinationaliste et non-idéologue (selon la théorie de la conciliation de Marx) pour comprendre le handicap. Cette étude utilise le contexte global de l’économie capitaliste et de la politique impérialiste des États-Unis et de l’Europe au Moyen-Orient pour comprendre comment les corps handicapés sont générés par les conflits armés entretenus par les relations sociales impérialistes et nationalistes. Cette étude engage la dialectique de la géopolitique, les examine dans le contexte de la guerre, et propose un nouveau modèle pour les études sur les incapacités du point de vue des femmes du Moyen-Orient survivantes de la guerre. Mots clefs Non-idéologique; guerre Iran-Irak; l’impérialisme handicapant; nationalisme handicapant; modèle d’incapacité transnationale; tiers-monde